Response of on farm produced organic inputs on soil, plant nutrient status, yield and quality of guava (Psidium guajava) cv Allahabad Safeda - RAM, R A; SINGHA, ATUL; BHRIGUVANSHI, S R (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2008-09 to compare the efficacy of different organic inputs in the production of guava (Psidium guajava L.) cv Allahabad Safeda. The highest number of fruits (363/tree) and yield (41.45 kg/tree) was recorded by application of 250 g rhizospheric soil of Ficus bengalensis + 5% Amritpani + organic mulching followed by 328 fruits/tree and yield of 31.76 kg/tree by biodynamic compost (30 kg/tree). Maximum TSS (11.7 °Brix) in fruits was recorded through application of biodynamic compost fortified with BD-500 (30 kg/tree) and cow pat pit (100 g/tree) followed by 11.3 °Brix with of vermicompost (30 kg/tree) + Azospirillum culture (250 g/ tree) + PSB (50 g/tree). The treatments did not affect acidity, ascorbic acid and reducing sugars significantly. Microbial analysis of different organic inputs indicated that cow pat pit contained maximum load of Azotobacter sp (1.5 × 106 cfu/g) and Azospirillum sp (1.3 × 106 cfu/g). Rhizospheric soils of Ficus bengalensis contained maximum number (1.5 × 105 cfu/g) of Azotobacter and (1.4 × 107 cfu/g) Azospirillum as compared to mango (2 × 104 cfu/g and 1.2 × 104 cfu/g, respectively). After two years of experimentation, maximum organic carbon (0.818%) was recorded in the basin soil of treatment biodynamic compost fortified with BD-500 (30 kg/tree) and cow pat pit (100 g/tree). On the other hand, highest build of available P (67.6 ppm) was maximum with application of biodynamic compost @ 30 kg/ tree, while available K (384 ppm), Zn (14.12 ppm), Cu (11.20 ppm) and Fe (15.7 ppm) were maximum with application of biodynamic compost fortified with BD-500 (30 kg/tree) and cow pat pit (100 g/tree), compared to initial soil nutrient status. Improvement in leaf nutrient status was also noticed and maximum leaf N (1.68%), P (0.244%), K (1.74%), Ca (1.49%), Zn (33.8 ppm) with application of rhizospheric soil of Ficus bengalensis @ 250 g/tree + 5% Amritpani + organic mulching, Mg (0.63%); with vermicompost (30 kg/tree) + Azospirillum culture (250 g/tree) + PSB (50 g/tree), Cu (78.7 ppm) and Mn (195.1 ppm) were recorded with FYM (30 kg/tree as compared to control (1.21%, 0.212%, 1.23%, 1.33%, 0.21 ppm, 27.5 ppm, 46.4 ppm and 167.6 ppm, respectively).